PERANAN KEPALA DESA DALAM MENGKOORDINASIKAN PEMBANGUNAN FISIK DI DESA TOPANG KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - Adi Susanto; Ahmad Tarmizi Yusa (UIR Press, 2018)
This study aims to determine the role of village head in coordinating physical development in the village Augments. The role of assessment indicators are used, among others, is Giving Guidelines, Giving Guidance, Referral Giving, and Giving Supervision. The location of this research is in the Village District of Stimulation Augments. Type a descriptive survey research with qualitative methods of data collection with the use of oral or written information of resources. There are two groups of the population and the sample in this study. 46 population of the village office perangkati prop is also in use as a sample. The sampling technique using the census for the village office. The technique of collecting data using interviews and questionnaire methods of observation. Data were analyzed by using a percentage table. Berdasarkaan results of research on the role of Head of Rural Development in the Physical Coordinate In the District Rural Supports stimuli produce Meranti Islands Regency kireteria assessment carried out in the category. Advice from the author, especially with regard to the role in coordinating the development of the village head is giving pedoaman, guidance, direction and supervision of the construction will be undertaken in order to run with done.